Electrical conductivity and total organic carbon analysis of water in Brazilian industrial pharmaceutical formulations - Daniela Toledo de Matos, Flávio Silva de Carvalho, Fernando Machado dos Santos (Journal of Applied Pharmaceutical Science, 2023)
A study was proposed with a new analysis routine performed for a month for the electrical conductivity and total organic carbon (TOC) parameters of the water used in the pharmaceutical industry based in the metropolitan area of Goiânia (central region of Goiás, Brazil) in order to evaluate the water quality according to the current legislation. In this sense, daily conductivity and TOC tests were carried out both in purified water and in water for injections during the month of March 2022. The result for the TOC analysis in purified water and water for injections was acceptable. For conductivity analysis in purified water and water for injections, there were samples with critical values to the upper limit, exceeding that specified by the Pharmacopoeia. Therefore, it is concluded that, for TOC analysis, the results are within the acceptance range; however, for conductivity, it will be necessary to open a failure analysis report to investigate possible analytical errors. The results presented open future perspectives regarding the rigor of the need for maintenance and qualification in the equipment of the quality control laboratory and to establish the validity of the system of purification, storage, and distribution of water used in pharmaceutical industries.
Keywords: Physical-chemical test, quality control, statistical analysis, industrial water